FFK "Solea" setzt FFS "Anton Dohrn"-Fahrten in die zentrale Ostsee fort - Tiews, K. (1975)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010